Duck House Inhalable Particulate Matter Induces Lung Injury by Activating Ferroptosis - Zhiyun Guo; Tongjie Chai; Luna Yu; Kuihao Liu; Zhengxiu Qu; Zhaopeng Zhang; Meiling Liu; Jianhua Qiu; Gang Wang; Ning Li (Poultry Science)
The particulate matter (PM) generated during poultry farming is characterized by its complex composition and substantial emission levels. However, researches on the respiratory damage caused by poultry house PM and the underlying mechanisms remain limited. In this study, inhalable PM collected from duck houses was administered to experimental mice through inhalation exposure. After 10 days of short-term exposure and 30 days of long-term exposure, mice samples were collected for lung histopathological analysis and inflammatory cytokines detection. The results showed that inhalation of duck house PM induced pulmonary and systemic inflammatory responses in both groups of mice, with significant upregulation of IL-6 and CXCL2. Compared to short-term exposure, long-term exposure resulted in more severe microscopic lesions in the lungs. In addition, the concentrations of malondialdehyde (MDA) and glutathione (GSH) increased in mice, indicating that duck house PM could trigger oxidative stress in lungs, we also found duck house PM induced ferroptosis in mice. Furthermore, it was confirmed that duck house PM caused cell damage and increased intracellular iron levels in MLE-12 cells, and PM reduced GSH in a dose-dependent manner. Notably, ferroptosis inhibitor treatment effectively alleviated PM-induced cell damage. These findings indicated that duck house PM can induce ferroptosis in both mice and cells, and ferroptosis plays a critical role in duck house PM-induced lung damage. These results laid a solid foundation for further exploring the mechanism of PM-induced lung injury, and providing a new insight for targeting ferroptosis to treat such damage.